2014
DOI: 10.1346/ccmn.2014.0620307
|View full text |Cite
|
Sign up to set email alerts
|

The Dissolution of Amorphous Silica in the Presence of Tropolone Under Acidic Conditions

Abstract: Dissolution of amorphous silica or silicate is an important reaction to release silicic acid in natural water and this reaction is affected by several factors. The existence of a natural organic compound, tropolone, because of its abundance, is of particular importance. In the present study, the dissolution of amorphous silica in the presence of tropolone (HL) was investigated in an aqueous solution under acidic conditions. The dissolution is controlled by the reaction between silicic acid and tropolone (Si(OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…387 The dissolution rate is generally increased with an increase in pH from 2 to 8.5 because when pH > 8.5, ions which are more soluble (SiO(OH) 3À ) are being developed. 388 The composition is also an equally important factor that helps in determining the dissolution rate of the glass. For example; Ma et al 60 reported that with partial substitution of MgO for CaO in the composition, the glass degradation rate decreases with the delay in HCA layer formation, which was ascribed to the effect of ionic eld strength and diverse bonding congurations of glass.…”
Section: àmentioning
confidence: 99%
See 1 more Smart Citation
“…387 The dissolution rate is generally increased with an increase in pH from 2 to 8.5 because when pH > 8.5, ions which are more soluble (SiO(OH) 3À ) are being developed. 388 The composition is also an equally important factor that helps in determining the dissolution rate of the glass. For example; Ma et al 60 reported that with partial substitution of MgO for CaO in the composition, the glass degradation rate decreases with the delay in HCA layer formation, which was ascribed to the effect of ionic eld strength and diverse bonding congurations of glass.…”
Section: àmentioning
confidence: 99%
“…387 The dissolution rate is generally increased with an increase in pH from 2 to 8.5 because when pH > 8.5, ions which are more soluble (SiO(OH) 3− ) are being developed. 388…”
Section: Properties Of Sol–gel Derived Porous Glassesmentioning
confidence: 99%
“…The equilibrium concentration of Si(OH) 4 (in parts per million) is 70 ppm at 25 °C for massive amorphous silica. 57 It was reported that organic compounds can interact with Si(OH) 4 or a silica surface to notably increase the dissolution concentration in water, 59 and the organic contaminants adsorbed on the cantilever and sample surfaces may have such an effect. As can be seen from Figure 3e, the C peak intensity in the contact zone is high, while that outside the contact zone is low.…”
mentioning
confidence: 99%